Water Content Detector In The Soil In A Pot To Warned Using Arduino IoT Cloud - Yohan Husnira, Ridho; Rivaldi, Rivaldi (Journal of Computer Science and Informatics Engineering, 2023)
In daily life, people who have a hobby of farming of course have plants that need to be cared for every day. One of the most important forms of care to consider is watering. There are some people who sometimes forget that their crop soil is moist or dry. In this research, soil moisture sensor is used as a device for detecting soil moisture and will be combined with DHT11 and DFPlayer Mini module in its design. NodeMCU ESP8266 is connected to a soil moisture sensor to determine soil moisture, a DHT11 sensor to determine air temperature and humidity and a DFPlayer Mini module as a media player for watering warning audio files. The speaker driver is connected to the DFPlayer Mini module as the sound output medium of the alert. 2 of 18650 batteries connected to the NodeMCU ESP8266 to power the NodeMCU ESP8266 and the device as a whole. These devices can be monitored remotely and integrated with the cloud.